Peripheral immune characteristics of hepatitis B virus-related hepatocellular carcinoma - Sun, Ruonan; Li, Jiawei; Lin, Xianyi; Yang, Yidong; Liu, Bing; Lan, Tianbi; Xiao, Shuang; Deng, Anyi; Yin, Zhinan; Xu, Yan; Xiang, Zheng; Wu, Bin (Frontiers in Immunology, 2023)
Background Liver cancer is the sixth most common cancer worldwide and the third leading cause of cancer-related death. As a chronic liver disease, many studies have shown that the immune response plays a key role in the progression of liver cancer. Chronic hepatitis B virus (HBV) infection is one of the high-risk factors for HCC, accounting for 50%–80% of HCC cases worldwide, and little is known about the immune status of HBV associated hepatocellular carcinoma (HBV-HCC), therefore, we aimed to explore the changes in peripheral immunity in patients with HBV-HCC. Methods In this study, patients with HBV-HCC (n=26), patients with hepatitis B-related cirrhosis (HBV-LC) (n=31) and healthy volunteers (n=49) were included. The lymphocytes and their subpopulation phenotypes in peripheral blood were characterized. In addition, we explored the effect of viral replication on peripheral immunity in patients with HCC and analyzed the circulating immunophenotypic characteristics at different stages of HCC with flow cytometry. Results Firstly, our results showed that the percentages of total αβ T cells in the peripheral blood of HBV-HCC patients was significantly decreased compared to healthy subjects. Secondly, we found that naïve CD4+ T cells in HBV-HCC patients were significantly reduced, terminally differentiated CD8+ T cells, homing memory CD8+ T cells and Th2 cells were increased in peripheral circulation in HBV-HCC patients. Moreover, in the peripheral blood of HBV-HCC patients, expression of TIGIT on CD4+ T cells and PD-1 on the surface of Vδ 1 T cells was increased. In addition, we found that sustained viral replication resulted in up-regulation of TIM3 expression on CD4+ T cells, and TIM3+ γδ T cells increased in peripheral circulation in patients with advanced HBV-HCC. Conclusion Our study showed that circulating lymphocytes in HBV-HCC patients exhibited features of immune exhaustion, especially in HCC patients with persistent viral replication and in patients with intermediate and advanced HBV-HCC, including decreased frequency of T cells and elevated expression of inhibitory receptors including TIGIT and TIM3 on CD4+ T cells and γδ T cells. Meanwhile, our research suggests that the combination of CD3+ T cell and CD8+HLADR+CD38+ T cell may be a potential diagnostic indicator for HBV-HCC. These findings could help us to better understand the immune characteristics of HBV-HCC and explore the immune mechanisms and immunotherapy strategies for HBV-HCC.